(untitled) (Revista Brasileira Multidisciplinar, 2024)
The use of probiotic spore-forming bacteria, such as Bacillus spp., has increased due to their ability to form spores resulting in greater resistance during production, storage and commercialization processes. Bacillus clausii has been on the market for over 55 years and is characterized by the presence of four probiotic strains (O/C, SIN, N/R and T). In this study, Bacillus clausii , from the commercial product Enterogermina ®, was obtained from pharmacies and drugstores in the city of Dourados-MS. To characterize Bacillus clausii for use as a probiotic, pH 2 and 3 analysis, tolerance test and hydrolysis of bile salts at 0.3%, pepsin and pancreatin tolerance test, adhesion test and hemolysis activity were performed. In the analyzes of tolerance to acidic pH, bile salts, pepsin and pancreatin, there were no significant differences compared to the log CFU/mL -1 of initial cells. 67% of adherence to stainless steel sheet. It showed bile salt hydrolysis and γ-hemolytic activity in blood agar. Thus indicating great probiotic potential.